Primary education from the perspective of decolonial epistemologies in Brazil and latin america: culture and knowledge in science education in the decolonial curriculum in action in quilombola school education (Research, Society and Development, 2023)
Quilombola School Education has its decolonial genesis in the entire educational process, in which it proposes a teaching that values and recognizes in educational practices rooted in the theoretical basis of ancestral knowledge in Sciences built by collectives of subjects in their ethno-educational territories and, it is justified based on Law 10.639/2003 and its specific guidelines. The article sets out to present learning situations in the curriculum in action in the teaching of the aforementioned discipline, having as a guiding principle their sociocultural knowledge. The guiding question for the research was: if teaching mediated with pedagogical, methodological and didactic practice with decolonial epistemology and within its cultures and knowledge has potential for teaching its traditional knowledge in Science? The research fits into the qualitative approach and procedures of the participant research carried out in 2022 with students in the final years of Elementary School, in a School of the Municipal Public Network located in the State of Espírito Santo-ES. The data collection technique was semi-structured interviews with a focus group and non-participant observations of Science classes. Data were analyzed through content analysis; It appears that in the curriculum in action, the teaching of Science was aligned with the current legal and educational frameworks. It was verified in the observations the use of decolonial ancestral knowledge in Sciences of the Elders about the production of beju in practical classes on sugars with articulation with scientific knowledge. We conclude that decolonial teaching corroborated the strengthening of the students' ethnic and cultural identity.